Cascade Control of Antagonistic VSA—An Engineering Control Approach to a Bioinspired Robot Actuator - Lukić, Branko; Jovanović, Kosta; Šekara, Tomislav B. (Frontiers in Neurorobotics, 2019)
A cascade control structure for the simultaneous position and stiffness control of antagonistic tendon driven VSAs implemented in a laboratory setup is presented in the paper. Cascade control has the ability to accelerate, additionally stabilize and reduce oscillations, all extremely important in systems such as a tendon-driven compliant actuators with the elastic transmission. Inner-loop controllers are closed in terms of motor positions, and outer-loop controllers in terms of actuator position and estimated stiffness. The dominant dynamics of the system (position and stiffness), comprised of the mechanical part and inner loops, are identified by a closed-loop ARX model. The outer-loop controllers are tuned on the basis of experimentally identified transfer functions of the system, in several nominal operating points for different stiffness values. After the system is identified, a controller bank is generated in which a pair of actuator position and stiffness controllers correspond to a nominal operating point and covers the area surrounding the nominal point for which it is designed. The controllers used are I-PD and I-P controllers which are a variation of the PID and PI controllers with dislocated proportional and derivative gains from direct to feedback branch that result to no overshoot for even for fast reference changes (i.e. step signal) which is essential for preventing tendon slackening (meeting the pulling constraint).; Analytical formulas for controller tuning based on only one parameter - λ are also presented. Since position and stiffness loops are decoupled, it is possible to change λ for both loops independently and adjust their performance separately according to the needs. Also, the controller structure secures the smooth response without overshoots step reference or step disturbance signal, which make practical implementation possible. After all the controllers were designed, the cascade control structure for simultaneous position and stiffness control was successfully evaluated in a laboratory setup. Thus, the presented control approach is simple to implement, but with the performance which ensures a pulling constraint for tendon driven actuators as a foundation for bio-inspired antagonistic VSAs.